Economic Growth Dynamics in West Nusa Tenggara Province: Investment, Gross Regional Domestic Product, and Government Finance - Jasman, Jasman; Hwihanus, Hwihanus (Jurnal Ilmiah Manajemen Kesatuan, 2023)
West Nusa Tenggara (NTB) plays a pivotal role in Indonesia's economy, driven by cultural diversity and natural resources. Sustaining economic growth is crucial for the region. NTB's economic dynamics, influenced by inflation, banking, investments, GRDP, and government finances, exhibit unique patterns. This research investigates NTB's economic growth, exploring its connections to inflation, banking, investments, GRDP, and government finances. Stable inflation, along with investments and government finances, significantly influences NTB's economic trajectory, offering insights into regional economic stability and community purchasing power. The study provides valuable perspectives on the multifaceted factors shaping West Nusa Tenggara's economic landscape. Secondary data from the Central Bureau of Statistics (BPS) and Bank Indonesia (BI) is utilized, employing a Non-Probability sampling technique, specifically Convenience sampling. Data collection involves observation, structured interviews, and literature studies. Quantitative analysis using SPSS Version 26 concludes that economic growth dynamics in West Nusa Tenggara are interrelated, with varying significance levels among factors such as inflation, banking performance, investments, GRDP, and government finances. Stable inflation emerges as a significant factor influencing economic growth in the province, alongside investments, GRDP, government finances, and banking performance.